The Influence of Natural Resource Potential and Sovereign Wealth Fund Strategy on Organizational Performance: The Mediating Role of Human Resource Strategy in Indonesia - Fahlevi, Raden Muhamad Rizza; Usman, Bahtiar; Anggiani, Sarfilianty (Research Collaboration Community (RCC), 2025)
This purpose of this study is to examines the mediating role of Human Resource Strategy in the relationship between Natural Resource Potential (Renewable Energy), Sovereign Wealth Fund Strategy, and Organizational Performance in Indonesia. Using a correlational quantitative method, a non-probability sampling approach, and purposive sampling, the study targets managerial officials in government agencies and state-owned enterprises (SOEs) in the renewable energy sector. The final sample consists of 143 respondents, with cross-sectional data collected via an online survey. Data analysis is conducted using Structural Equation Modeling (SEM-PLS) with SmartPLS version 4. Findings reveal that HR Strategy not only has a dominant direct influence on organizational performance but also mediates the impact of Natural Resource Potential and SWF Strategy. This underscores the importance of synergy between resource management, strategic financial policies, and human competency development in driving the energy transition. The study extends the Resource-Based View through a dynamic capability approach, highlighting that competitive value depends not only on resource ownership but also on HR adaptability. It also redefines SWF as an institutional entrepreneur, transforming macro policies into micro-level actions. However, the study’s focus on the renewable energy sector and government agencies/SOEs limits generalization. Future research should expand to other sectors, integrate contextual variables like energy decentralization policies, and adopt qualitative methods to explore HR Strategy and SWF implementation. Practical recommendations include improving HR training in green technology, enhancing SWF allocation transparency, and fostering synergy between national and local policies to support renewable energy targets.